Heterogeneous myocyte remodelling and spatial heterogeneity of repolarization within the myocardial infarction border zone. (19th May 2022) - Amoni, M; Vermoortele, D; Ekhteraeitousi, S; Donate Puertas, R; Ingelaere, S; Roderick, H L; Claus, P; Willems, R; Sipido, K R
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Fund for Scientific Research-Flanders (FWO) Background: Sudden cardiac death due to ventricular arrhythmias is a major cause of mortality after myocardial infarction (MI). The border zone (BZ) surrounding the infarct is the dominant source of arrhythmias. Here a substrate of heterogeneous repolarization is implicated, which could be due to heterogeneous myocyte remodelling. Objective: To examine myocyte remodelling within the BZ, in comparison to the remote myocardium, and evaluate the local profile of repolarization of these regions in vivo. Methods: MI was induced by 120-minute occlusion of the left anterior descending coronary artery followed by reperfusion in 6 domestic pigs. After 4 weeks, magnetic resonance imaging was performed to assess infarct remodelling and local wall thickness. Within 3 days, electro-anatomical mapping was performed. A non-contact recording of a 64-electrode array was translated to 2048 electrograms distributed over the LV and local activation-recovery-interval (ARI) determined by custom software. After recovery (2-4 days), the pigs were sacrificed, and samples collected from the BZ and remote region for RNA analysis and single cardiomyocyte isolation. Cell dimensions were measured and cellular AP duration (APD) was optically recorded using a fluorescent voltage dye, Di-8-Annepps (stimulation at 1Hz, 37°C). Expression and variability of cardiomyocyte hypertrophy biomarkers were extracted from single nuclear RNA sequencing data (10x Genomics). Results: Cardiomyocyte APD in large population samples (> 100 cells per region in each pig) revealed higher heterogeneity in the BZ than the remote region, quantified as the standard deviation (SD) (BZ: 105.9 ± 17.0ms vs remote: 73.9 ± 8.6ms, P = 0.001). Cellular APD heterogeneity correlated strongly with in vivo local ARI heterogeneity, which demonstrated increased heterogeneity in the BZ (R2 = 0.67, P = 0.002). BZ myocytes were hypertrophied with greater increase in cell width than length, and cellular hypertrophy was more heterogeneous by SD in the BZ (BZ: 12.9 ± 2.4μm vs remote: 8.3 ± 1.1μm, P < 0.001). NPPB transcripts reporting on hypertrophic remodelling were higher in BZ than remote (mean lognorm gene expression, BZ: 0.431 ± 0.014 vs remote: 0.107 ± 0.004, P < 0.001), and showed greater heterogeneity in expression between cells by proportion of hypertrophic (NPPB +ve) cells (BZ: 30.86% vs remote: 8.37%, P < 0.001). Wall thickness variance was higher in the BZ compared to the remote region (anterior BZ: 0.15 ± 0.02mm, septal BZ: 0.16 ± 0.04mm vs remote: 0.04 ± 0.02mm, P < 0.001), contributing to increased heterogeneity of local wall stress in BZ. Conclusion: Cardiomyocyte remodelling in the BZ is heterogeneous, possibly related to differences in local wall stress, which may contribute to heterogeneous repolarization in vivo and underlie arrhythmia vulnerability within the BZ.